Synthesis and rheology of ferrofluids: a review - GENÇ, SEVAL (ELSEVIER SCI LTD, 2014)
There is no doubt about the potential technological significance of ferrofluids. The promising applications have been identified as dynamic sealing, heat dissipation, damping, and doping of technological materials. Ferrofluids are known as magnetic liquids that are colloidal suspensions of ultrafine, single domain magnetic particles in either aqueous or non-aqueous liquids. In this review article a general classification and the main properties of ferrofluids, description of their synthesis in terms of stability and rheology, and how it is understood in various parts of the science and technology are given. Then the structural changes and rheological properties of these smart fluids under an external stimulus together with a series of applications are presented.
Keywords: IRON; NANOPARTICLES; STABILITY; PARTICLES